Three new species of Convolvulaceae Juss. from South America - Ferreira, Priscila Porto Alegre; Simão-Bianchini, Rosangela; Miotto, Silvia Teresinha Sfoggia (Phytotaxa, 2013)
Studies concerning Convolvulaceae in southern Brazil have revealed many novelties, such as new species and range extensions. In the present paper, three new species are described: Calystegia brummittii, Convolvulus ensifolius and Ipomoea mirabilis. Descriptions, illustrations and data on species distribution and conservation status are provided.